Land development in turkey: A model on the subdivision in urban areas - Sevkiye Sence Turk (European Regional Science Association (ERSA), 2001)
The main objective of the subdivision in urban areas is to constitute the healthy urban structure, to provide land development and to regulate the use of private and public land for public interest. The other important objective is to prevent sprawl of city and chaotic growth. Especially, subdivision is an important tool for applying of physical planning decisions into urban space in Turkey. Municipalities are responsible for the application of land subdivision according to detailed urban plans except a voluntary basis through agreements according to civil law. But there is lack of sufficient research related to realizing of subdivision in urban spaces throughout the Turkey. The purpose of this paper is to determine whether there is a difference in realizing of subdivision according to detailed planning decisions between urban areas in different population groups. The additional purpose of this paper is to constitute a model concerning application of subdivision according to detailed urban planning for urban areas in different population groups in Turkey and then to compare each of these city groups. For this research, a sample survey method is used and 480 questionnaires are completed by Planning Office of the Municipalities of urban areas in different population groups. In this model the realizing of subdivision index (RSI) are used as a dependent variable and population, population growth ate, global density in urban areas according to detailed plans, Municipal budgets, socio-economic index, the average of land values of cities. Multiple Regression Model is utilized for each city groups and comparison tables. The results of the paper can be used to identify the problems concerning subdivision regulation in Turkey and to suggest solutions these problems based on existing legislation in Turkey.
Keywords: 330